2021
DOI: 10.1039/d1nr05048f
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected hydrophobicity on self-assembled monolayers terminated with two hydrophilic hydroxyl groups

Abstract: An unexpected hydrophobicity with a contact angle of 82° on (OH)2-SAM terminated only with two hydrophilic OH groups was found, which is attributed to the formation of a hexagonal-ice-like H-bonding structure in the OH matrix of (OH)2-SAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The model atoms at the other end of the alkyl chains were bound to a (111) facet of a face-centered cubic (FCC) lattice. The packing densities were 4.5 nm À2 and 6.5 nm À2 , corresponding to the hydrophobic and hydrophilic structures in our previous study, 24 respectively. The protein solvated by the SPC/E 25 water molecules was initially placed at 6 Å above the (OH) 2 -SAM.…”
Section: Modelssupporting
confidence: 57%
See 3 more Smart Citations
“…The model atoms at the other end of the alkyl chains were bound to a (111) facet of a face-centered cubic (FCC) lattice. The packing densities were 4.5 nm À2 and 6.5 nm À2 , corresponding to the hydrophobic and hydrophilic structures in our previous study, 24 respectively. The protein solvated by the SPC/E 25 water molecules was initially placed at 6 Å above the (OH) 2 -SAM.…”
Section: Modelssupporting
confidence: 57%
“…It is worth noting that the researchers 23 found that the SAM terminated with only a hydrophilic OH group could resist peptide adsorption among the SAMs terminated with four different hydrophilic and hydrophobic groups (i.e., CH 3 , NH 2 , COOH, and OH), and the hydrophobic CH 3 -terminated SAM did not exhibit resistance to peptide adsorption. It is found that the structure of the hydrophobic SAM 24 itself terminated with only hydrophilic OH groups can significantly improve the performance of resistance to protein adsorption in our current study compared with their results of the OH-terminated SAM resistance to peptide adsorption. Therefore, the hydrophobic OH-terminated SAM is very suitable for resisting protein adsorption in our study.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…This physical barrier effect was traditional mechanistic explanation for OH-SAM resistance to protein adsorption. However, our previous study [15] found that SAM terminated with only hydrophilic OH groups exhibited different hydrophilic and hydrophobic characteristics at different pack-ing densities. For such structures, is the effect of interfacial water on OH-SAM resistance to protein adsorption consistent?…”
Section: Introductionmentioning
confidence: 91%